Planning and Providing Acute Stroke Care in England: The Effect of Planning Footprint Size - Allen, Michael; Pearn, Kerry; Villeneuve, Emma; James, Martin; Stein, Ken (Frontiers in Neurology, 2019)
Background: The policy of centralising hyperacute stroke units (HASUs) in England aims to provide stroke care in units that are both large enough to sustain expertise (>600 admissions/year) and dispersed enough to rapidly deliver time-critical treatments (<30 minutes maximum travel time). Currently, just over half (61%) of stroke patients access care in units with at least 600 admissions per year and 56% attend such a unit and have a travel time of no more than 30 minutes. Objective: We have sought to understand how varying the planning and provision footprint in England affects access to care whilst achieving the recommended admission numbers for hyper-acute stroke care. We have compared two different planning footprints to national-level planning: planning using five NHS Regions in England, and planning using 44 Sustainability and Transformation Partnerships (STPs) in England. Methods: Computer modelling and optimisation using a multi-objective genetic algorithm. Results: The number of stroke admissions between STPs varies by seven fold, while the number of stroke admissions between NHS Regions varies by 2.5 fold. In order to meet stroke admission guidelines (600/year) for all units the maximum possible proportion of patients within 30 minutes would be 82%, 78% and 72% with no boundaries to planning/provision, NHS Region boundaries, and STP boundaries (in these scenarios patients cannot move outside of their own STP or NHS Region). If STP or NHS Region boundaries are removed for provision of service (after planning is performed at these local levels), travel time is improved, but number of admissions to individual hospitals become significantly changed, especially at STP planning level where admission numbers per unit changed by an average of 204 (19%), and not all units maintained 600 admissions after removal of boundaries. Conclusion: Planning and providing services at STP level could lead to sub-optimal service provision compared with using larger and more consistently populated planning areas.